Description of Postural Strategies through a Variable Structure Control - Tigrini, Andrea; Mengarelli, Alessandro; Cardarelli, Stefano; Strazza, Annachiara; Nardo, Francesco Di; Fioretti, Sandro; Verdini, Federica (Conference proceedings (IEEE Engineering in Medicine and Biology Society. Conf.), 2019)
Human postural strategies in balance maintenance are the results of the complex control action played by the Central Nervous System (CNS). Literature underlined that such strategies become more evident when external perturbations challenge the stance. In this study, a new model of balance maintenance under support base movement perturbation is formulated. A sliding mode approach is employed to simulate the aforementioned strategies in stabilizing a double inverted pendulum, used to describe the mechanics of the bipedal human stance. Control parameters are then optimized in order to reproduce the measured center of mass (COM) displacement in the anterior-posterior direction. Such parameters seem to be useful to distinguish different postural strategies employed by different subjects. Moreover, electromyographic data are employed to effectively support the goodness of the model.